2000
DOI: 10.1111/j.1528-1157.2000.tb00203.x
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Facilitates Kainic Acid—Induced, but not Flurothyl‐Induced, Behavioral Seizure Activity in Adult Female Rats

Abstract: Summary:Purpose: This study was designed to determine whether previously demonstrated increases in hippocampal axospinous synapse density and NMDA receptor function induced by estradiol are paralleled by increased susceptibility to limbic (kainic acid induced) or generalized (flurothyl induced) behavioral seizures.Methods: Kainic acid was injected systemically to ovariectomized adult female rats treated with either estradiol or oil vehicle. The latencies to each of five stages of seizure-related behaviors (sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 38 publications
2
57
1
1
Order By: Relevance
“…We demonstrated that testosterone modulation of seizure susceptibility occurs through its conversion to neurosteroids with "anticonvulsant" and "proconvulsant" actions, and hence the net effect of testosterone on neural excitability and seizure activity depends on the levels of distinct testosterone metabolites within the brain (Reddy, 2004c). Unlike 17β-estradiol, which generally facilitates seizures (Backstrom, 1976;Hom and Buterbaugh, 1986;Buterbaugh, 1989;Woolley, 2000), 3α-androstanediol has been shown to produce powerful antiseizure effects (Reddy, 2004bc;Kaminski et al 2005), which are not mediated by the intracellular ARs (Cunningham et al, 1979;Roselli et al, 1987). To determine the pathways of neurosteroid synthesis (see Fig.1), the following agents were used: (i) Letrazole, an inhibitor of the aromatase enzyme (Bhatnagar et al, 1990;, was used to block conversion of testosterone to 17β-estradiol; (ii) Finasteride, an irreversible inhibitor of both type 1 (brain) and type 2 (peripheral tissues) 5α-reductase isozymes in rodents (Azzolina et al, 1997), was utilized to inhibit the conversion of testosterone into DHT; (iii) Indomethacin, a powerful blocker of 3α-HSOR enzyme activity 1983;, was used to inhibit reduction of DHT into 3α-androstanediol.…”
Section: Resolving Bimodal Effects Of Testosterone On Seizure Susceptmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that testosterone modulation of seizure susceptibility occurs through its conversion to neurosteroids with "anticonvulsant" and "proconvulsant" actions, and hence the net effect of testosterone on neural excitability and seizure activity depends on the levels of distinct testosterone metabolites within the brain (Reddy, 2004c). Unlike 17β-estradiol, which generally facilitates seizures (Backstrom, 1976;Hom and Buterbaugh, 1986;Buterbaugh, 1989;Woolley, 2000), 3α-androstanediol has been shown to produce powerful antiseizure effects (Reddy, 2004bc;Kaminski et al 2005), which are not mediated by the intracellular ARs (Cunningham et al, 1979;Roselli et al, 1987). To determine the pathways of neurosteroid synthesis (see Fig.1), the following agents were used: (i) Letrazole, an inhibitor of the aromatase enzyme (Bhatnagar et al, 1990;, was used to block conversion of testosterone to 17β-estradiol; (ii) Finasteride, an irreversible inhibitor of both type 1 (brain) and type 2 (peripheral tissues) 5α-reductase isozymes in rodents (Azzolina et al, 1997), was utilized to inhibit the conversion of testosterone into DHT; (iii) Indomethacin, a powerful blocker of 3α-HSOR enzyme activity 1983;, was used to inhibit reduction of DHT into 3α-androstanediol.…”
Section: Resolving Bimodal Effects Of Testosterone On Seizure Susceptmentioning
confidence: 99%
“…Generally, 17β-estradiol produces excitatory effects and thereby facilitates seizures (Woolley, 2000), while 3α-androstanediol has neuroprotective and antiseizure activity (Reddy, 2004b). Therefore, a detailed study of 3α-androstanediol and related neurosteroids as mediators of the physiological effects of testosterone is required to establish the pathophysiological role of androgenic neurosteroids in the brain function.…”
Section: α-Androstanediol Is a Neurosteroidmentioning
confidence: 99%
“…Numerous studies over the last few decades have identified sex and cycle-dependent differences in seizure susceptibility in rodents. These studies have used various methods to induce seizures, including kindling, electroshock, and chemoconvulsant administration Buterbaugh, 1989;Edwards et al, 1999;Finn and Gee, 1994;Hoffman et al, 2003;Hom and Buterbaugh, 1986;Hudson and Buterbaugh, 1991;Kalkbrenner and Standley, 2003;Matejovska et al, 1998;Nicoletti et al, 1985;Pericic and Bujas, 1997;Persinger et al, 1988;Pesce et al, 2000;Schwartz-Giblin et al, 1989;Slamberova and Vathy, 2000;Tan and Tan, 2001;Tominaga et al, 2001;Valente et al, 2002;Velisek et al, 1999;Wahnschaffe and Loscher, 1992;Woolley, 2000). However, these studies have failed to provide a clear picture of the relationship between ovarian hormone levels and seizure susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent work, however, has shown that proconvulsant effects of estrogen, as well as anticonvulsant effects of progesterone, may depend to a large extent on the specific experimental conditions used. For example, although there have been repeated demonstrations that estrogen is proconvulsant (Buterbaugh, 1989;Matejovska et al, 1998;Nicoletti et al, 1985), there is also evidence that this is not the case (Hoffman et al, 2003;Hom and Buterbaugh, 1986;Hudson and Buterbaugh, 1991;Slamberova and Vathy, 2000;Velisek et al, 1999;Woolley, 2000). Furthermore, while estradiol may protect neurons from seizureinduced neuronal damage (Azcoitia et al, 1998;Veliskova et al, 2000), this protective effect may not be mediated by a decrease in seizure severity (Hoffman et al, 2003;Reibel et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen treatment can decrease the threshold for hippocampal seizures (15). The simultaneous excitation of two different CA1 cells by the same terminal bouton in estrogen-treated animals would be expected to increase the synchronization of firing that can lead to seizure (16). Perhaps steroid analogs could be developed to counteract these seizure-facilitating effects of estrogen without interfering with the beneficial effects of the steroid.…”
mentioning
confidence: 99%